(untitled) (Colombia Medica, 1993)
The renin-angiotensin system functions a an important regulator of cardiovascular homeostasis. When recently discovered, it was considered a circulating endocrine system. Nowadays, it’s known that many of their constituents are synthesized in several] tissues, exerting such different roles on them that they have been classified in circulating and titular systems. The main organs it is localized are the heart, brain, kidney, blood vessels, adrenals, etc., where its functions are fairly established. However, the physiologic role of the system at the organs associated with reproduction is not so clear, despite the ANG II receptor localization on them.